Development of Chinese Version of Polycystic Ovary Syndrome Health-Related Quality of Life Questionnaire (Chi-PCOSQ) - Ou, Huang-tz; Wu, Meng-Hsing; Lin, Chung-Ying; Chen, Pei-Chi (PLOS ONE, 2015)
Objectives To develop the Chinese version of the Polycystic Ovary Syndrome Health-related Quality of Life Questionnaire (Chi-PCOSQ). Research Design and Method This cross-sectional study was conducted in a medical center in Taiwan. Eighty women who met the criteria were enrolled: female, age range of 18–45 years, competent in the Chinese language, had been diagnosed with polycystic ovary syndrome (PCOS), and were regularly followed at outpatient clinics (defined as at least two outpatient visits before enrollment). The PCOSQ was translated and culturally adapted according to standard procedures. A semi-structured interview was applied to assess face validity. Exploratory factor analysis (EFA) was applied to determine scale constructs. Measurements of internal consistency via Cronbach’s α, test-retest reliability via intraclass correlation coefficient (ICC), construct validity, and discriminative validity were performed. Results Five additional items, representing the issues of acne, hair loss, and fear of getting diabetes, were incorporated into the original scale. A six-factor structure emerged as a result of the EFA, explaining 71.9% of the variance observed. The reliability analyses demonstrated satisfactory results for Cronbach’s α ranging from 0.78–0.96, and for ICC ranging from 0.73–0.86. Construct validity was confirmed by significant correlation between the domains of the Chi-PCOSQ and generic health-related quality of life (HRQoL) measures (WHOQOL-BREF, EQ-5D) and clinical parameters (body mass index, waist-hip ratio, blood pressure). The known-group analysis indicated that the Chi-PCOSQ is a discriminative tool that differentiates patients according to their HRQoL. Conclusion The Chi-PCOSQ seems internally consistent, culturally acceptable, and our preliminary evidence suggests that it may be reliable and valid. The Chi-PCOSQ is a promising assessment tool to address the HRQoL of women affected by PCOS in Chinese-speaking countries and to further identify ethnic/cultural differences in the HRQoL of women with PCOS.